Databook of surface modification additives - Wypych, George (ChemTec Publishing, 2023)
"Eleven groups of additives are commercially available for improvement and surface modification of manufactured materials. These include additives improving anti-scratch and mar resistance, gloss, surface flattening, tack reduction, tack increase (tackifiers), surface tension reduction and wetting, surface cleaning, hydrophobization, anti-cratering, and leveling, dirt pickup resistance, and coefficient of static friction. A large number of final products benefit from the application of these additives, with major groups of industrial products including adhesives, appliances, automotive, bookbinding, building and construction, business machines, cellular phones, coatings, concrete, electronics, flooring, footwear, furniture, graphic arts, lacquers, leather, optical films, packaging, paints, paper, plastics, printing inks, rubber, sealants, wire and cable, and wood."-- Provided by publisher.
Keywords: Coatings.; Surfaces (Technology); elektronické knihy; electronic books